IMPLEMENTASI PROGRAM WOLBACHIA DALAM PENANGANAN KASUS DBD DI KOTA SEMARANG - Hilmi Arminta, Muhammad; Roestyaningsih, Dewi; Warsono, Hardi (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
The implementation of the Wolbachia program resulted in the discovery of several cases of dengue fever in Semarang City so that the spread of dengue fever cases in Semarang City has not been sufficiently controlled so this is a concern for the public. The aim of this research is to determine the implementation of the Wolbachia program in the community in Semarang City. Apart from that, to find out the driving and inhibiting factors related to the implementation of the Wolbachia program in Semarang City. The research results show that the Semarang City Health Service implements the Wolbachia program through five criteria, namely access, coverage, accuracy of services, accountability and resources. Based on the criteria that have been implemented at the Semarang City Health Service, only the access and coverage criteria are still not optimal, while the other criteria are already well implemented. Factors that need to be considered in implementing the Wolbachia program include communication, resources, disposition and bureaucratic structure. Recommendations that can be given are that socialization and education can be carried out with intensive information campaigns, training and workshops so that the insight expected by the government reaches the public and the provision of laboratories in Semarang City that are equipped with modern equipment.